Analisis Kebutuhan Media Pembelajaran IPAS Berbasis Kartu QR-TET Tumbuhan Terintegrasi Augmented Reality - Alfina, Zulfah Tahta; Sudarmin, Sudarmin; Rusilowati, Ani; Subali, Bambang; Lestari, Wahyu (SAP (Susunan Artikel Pendidikan), 2024)
This article aims to conduct a need analysis to teachers and grade IV students as a reference in order to produce augmented reality-based interactive learning media on the material of plant parts and functions, using qualitative descriptive methods and data collection techniques in the form of interviews, observations, and questionnaires. Data were obtained from 28 4th grade students of SDN Kejambon 10 as research respondents on May 8, 2024. Information collection was carried out using observation, interviews, and questionnaires. Based on the results of the needs analysis, it was found that students have difficulty in understanding science subjects, especially the material on plant parts and functions, so they need interactive learning media based on augmented reality that is interesting and facilitates their understanding, such as learning media for Plant QR-Tet Cards integrated with augmented reality which offers easy access, flexibility of time and place of learning. interesting and interactive display with visualization, attractive and interactive with visualization, flexibility of time and place of learning, Attractive and interactive displays with visualization, audio, video, and animation that can increase the interest and understanding of students, as well as the presentation of material in the form of quartet card games that are more interesting and increase the motivation of students to learn, so that overall the Plant QR-Tet Card is an innovative learning media that utilizes augmented reality technology to present material in a more interesting and interactive way.